2020
DOI: 10.1038/s41467-020-18991-8
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide screens identify Toxoplasma gondii determinants of parasite fitness in IFNγ-activated murine macrophages

Abstract: Macrophages play an essential role in the early immune response against Toxoplasma and are the cell type preferentially infected by the parasite in vivo. Interferon gamma (IFNγ) elicits a variety of anti-Toxoplasma activities in macrophages. Using a genome-wide CRISPR screen we identify 353 Toxoplasma genes that determine parasite fitness in naїve or IFNγ-activated murine macrophages, seven of which are further confirmed. We show that one of these genes encodes dense granule protein GRA45, which has a chaperon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
96
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(108 citation statements)
references
References 114 publications
6
96
1
Order By: Relevance
“…While the specific functions of these proteins are unknown, MYR1–4 all possess predicted transmembrane domains and may form a novel translocon ( Fig 5 ). An additional PV protein known as GRA45 is also required but appears to act broadly as a chaperone supporting dense granule secretion as well as insertion of PVM-resident membrane proteins such as MYR1-4 and thus its contribution to export is likely indirect [ 161 , 163 ]. Finally, ROP17, a kinase injected into the host cell from the rhoptries during invasion, is also necessary for export of dense granule effectors [ 164 ].…”
Section: Perspectives and Future Questionsmentioning
confidence: 99%
“…While the specific functions of these proteins are unknown, MYR1–4 all possess predicted transmembrane domains and may form a novel translocon ( Fig 5 ). An additional PV protein known as GRA45 is also required but appears to act broadly as a chaperone supporting dense granule secretion as well as insertion of PVM-resident membrane proteins such as MYR1-4 and thus its contribution to export is likely indirect [ 161 , 163 ]. Finally, ROP17, a kinase injected into the host cell from the rhoptries during invasion, is also necessary for export of dense granule effectors [ 164 ].…”
Section: Perspectives and Future Questionsmentioning
confidence: 99%
“…GRA45 was also identified in a CRISPR screen for genes necessary for Toxoplasma tachyzoites to survive in macrophages. This latter work showed that GRA45 has a chaperone‐like domain that is necessary for its role in moving GRAs across the PVM (Wang et al., 2020b). Thus, a total of eight proteins (MYR1‐4, GRA44/45, ROP17, and ASP5) are now known to all be required for this process.…”
Section: Translocation Of Gra Effectors Across the Pvm Is Mediated Bymentioning
confidence: 97%
“…There is a recent systematic review on effector translocation [ 110 ]; therefore, we will focus on updating the information in that review. A recently identified molecular chaperone GRA45, which has structural homology to the α-Crystallin domain of small heat shock protein, is necessary for transporting effector GRAs through the secretory pathway [ 111 ]. When GRA45 is deleted in T. gondii, other dense granule proteins (e.g., GRA5, GRA7, MAF1, GRA23, GRA16, and GRA24) are mislocalized to the vacuolar matrix and fail to be transported to the PVM and beyond [ 111 ].…”
Section: Translocation Of Gra Effectorsmentioning
confidence: 99%